If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8y + -9x + -6y = 0 Reorder the terms: 6x + -9x + -8y + -6y = 0 Combine like terms: 6x + -9x = -3x -3x + -8y + -6y = 0 Combine like terms: -8y + -6y = -14y -3x + -14y = 0 Solving -3x + -14y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14y' to each side of the equation. -3x + -14y + 14y = 0 + 14y Combine like terms: -14y + 14y = 0 -3x + 0 = 0 + 14y -3x = 0 + 14y Remove the zero: -3x = 14y Divide each side by '-3'. x = -4.666666667y Simplifying x = -4.666666667y
| x^4+18x^2+69= | | 8v-3v=25 | | -5x-7=11 | | 11x-3=10(x-5)-8 | | 4=5x-3 | | 6x^2-11x+5=3x+17 | | -x-42=4x+33 | | 126-36n=7+2n | | 6v-4=8(v-2) | | 73(3x)=10 | | -10x+2=12 | | 5x+8=4(x+6)+3 | | t^3+t^2-8m^3-4m^2=0 | | 2y-8=3y-10 | | 3(x-3)+2x-3=4x-8 | | 5x+4=8x-30 | | -2-42=4x+33 | | 15x*6=12 | | 62(30x-80)-43(52-20x)=377 | | -2k=1/4 | | x-14=5x+18 | | 4732-500=x | | 12x+5=11(x+7)+10 | | 7x-1=x-1+6x | | 2m-6=-1+m-4m | | 4(2x+10)=16 | | -1/2(3x-5)=7 | | -t^3-6t^2+12t+50=0 | | 5(x-5)-12=23x-127 | | x^2-2x+8=-12+7x | | 9h=-39 | | 3x+5=90 |